2019
DOI: 10.1016/j.semarthrit.2018.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid antibodies and renal transplant: A systematic review and meta-analysis

Abstract: Objective. To evaluate the effect of antiphospholipid antibodies (aPL) on renal allograft outcome after kidney transplantation. Methods. A systematic search of EMBASE and PubMed databases from inception to July 2018 was run according to PRISMA guidelines; Peto's odds ratio (OR) for rare events was used for the meta-analysis. Results. Our inclusion/exclusion criteria were met by 22 cohort studies having different outcomes: allograft thrombosis (n=9) and thromboprophylaxis (n=3), allograft loss from any cause (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Accordingly, the low heterogeneity displayed in the relation between LA and fistula occlusion might imply that the fluid phase coagulation assays detect a wider repertoire of aPL against native and oxidized lipid epitopes than aPL detected by solid‐phase immunoassays. The cessation of oxidative stress postrenal transplant may decrease or prevent the generation of these oxidized lipid epitopes, 64 which in turn may account for the disappearance of LA after the allograft, as previously shown 65 …”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the low heterogeneity displayed in the relation between LA and fistula occlusion might imply that the fluid phase coagulation assays detect a wider repertoire of aPL against native and oxidized lipid epitopes than aPL detected by solid‐phase immunoassays. The cessation of oxidative stress postrenal transplant may decrease or prevent the generation of these oxidized lipid epitopes, 64 which in turn may account for the disappearance of LA after the allograft, as previously shown 65 …”
Section: Discussionmentioning
confidence: 99%
“…Anti-cardiolipin antibodies have been associated with thrombotic risk, and its presence must be discarded in SLE patients. Also, a detailed assessment of cardiovascular history is of utmost importance due to the intrinsic cardiovascular risk of SLE [77]. Since LN patients are exposed to immunosuppressive treatment throughout their lives, the added exposure after a kidney transplant could increase the risk of neoplasms.…”
Section: Kidney Transplantation and Lnmentioning
confidence: 99%
“…Whether the "cool-down" effect also appears on aPL and leads to the lower prevalence of positive aPL in lupus patients with ESRD is an interesting topic for future research. Other studies have revealed that patients with positive aPL have a higher risk of thromboembolic events, which can further affect the circulation of kidney grafts [13][14][15]. In our study, only 1 patient had APS and progressed to GF.…”
Section: Discussionmentioning
confidence: 44%